ENGLISH PRONUNCIATION OF ENGLISH DEPARTMENT STUDENTS OF UNESA SEGMENTAL AND SUPRASEGMENTAL PERSPECTIVE - Inna Nur Laila; Ayunita Leliana (Universitas Negeri Surabaya, 2022)
Mispronunciation words, both segmental and suprasegmental features (stress), have been proved by some researchers. Meanwhile, this study is not only finding out those features that had been analyzed by previous researchers but also one more suprasegmental feature (intonation). Thus, this study’s objectives are to find mispronunciation in terms of both segmental (vowel and consonant) and suprasegmental (word stress and intonation) pronounced by fifteen students of English Department, Universitas Negeri Surabaya cohort 2018 who passed phonology and pronunciation classes. In this qualitative research, observation is applied to collect the data. The data were in the form of transcribed mispronunciation produced by the students and were analyzed using observation technique. Audio recording of reading a story aloud was the instrument for collecting the data. The result showed students committed pronunciation error in consonant /θ, v, ʒ, ʃ, ð, k, j/ vowel /a, ʌ, ɔ, ə, u, æ, ɪ/ and diphthong /aɪ, aʊ and eɪ/. The students placed primary stress on the first syllable of both noun phrases and compound nouns. Students committed intonation errors in falling tone occurred in imperative and WH-question, rising tone occurred in request and yes/no questions, and rising-falling tone occurred in strong emotion.